DISTRIBUSI LEBAH APIS KOSCHEVNIKOVI DI KALIMANTAN SELATAN (THE DISTRIBUTION OF APIS KOSCHEVNIKOVI IN SOUTH BORNEO) - Rohmatullah, Arif; Atmowidi, Rika Raffiudin Tri; Hadisoesilo, Soesilowati (Universitas Islam Darul Ulum, 2009)
This study aimed to explore the distribution of bees A. koschevnikovi in South Kalimantan. For this purpose, the researcher collecting bees A. koschevnikovi from several regencies in South Kalimantan. Banjar Regency (BJ), Tapin (TP), Upper South River (HSS), Hulu Sungai Tengah (HST) and Balangan (BL). From each district collected some colonies and each colony was taken approximately 80 individual bees. A. Bees koschevnikovi found living in hollow tree with height 0 - 2.5 m above the ground with distances between trees 1.5 - 3 m. In forests that have suffered damage from coal mining is not found in A. koschevnikovi.